Small holder farmers’ preferences in feedingcattle in ECER region, Malaysia - Amal Najim; Md. Ruhul Amin; S.M. Rezaul Karim; Soon Jan Mei (2015)
This study was conducted in ECER region Malaysia, which included, Kelantan, Pahang, Terengganu and part of Johor. The objective of this study was to identify the farmers’ preferences in feeding their cattle in this region. Data were collected by door to door survey usingstructured questionnaire as a tool for this study. A total of 289 small holder cattle farm families from 4 states of ECER were surveyed. From the result it appeared that number of beef cattle farm dominates over dairy in all states but there is regional difference in the ratio of beef to dairy farm. Highest proportion of dairy units are found in Johor (35.03%) and lowest in Terengganu (2.60%). Almost 52% farmers practice pasture grazing in main for feeding their cattle in Kelantan, 50% in Pahang, 44% in Kelantan and only 22% in Johor.An overall 6.57% farmers graze their cattle on road side.Very small % of farmers use treated or untreated straw to feed their cattle which indicate huge wastage of this kind of roughage. Feeding of silage is practised mainly in Johor (32.81%). Around 4-5% small holder farmers in Kelantan, Pahang and Terengganu provide green oil palm frond (OPF) as the main roughage feed to their cattle although it is the main cattle feed in large scale or integrated farming.Nearly 49% farmers in Kelantan maintain their animals without any concentrate feed. This % in Pahang, Johor and Terengganu is 35, 11 and 6 respectively. Of different types of grain, pellet or oil cakes palm karnel cake (PKC) occupied the first place because of its abundance not because of its price. Improved microbial, silage making or NPN technology is a potent ruminant feeding technology particularly in developing countries but these technolgy is only in practice in farmers of Johor in ECER region. This might be because of trained farmers in that area and because of abundance of dairy cattle.